2017
DOI: 10.3390/technologies5010006
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Accelerometer for Neonatal MRI Motion Artifact Correction

Abstract: Abstract:A wireless accelerometer has been used in conjunction with a dedicated 3T neonatal MRI system installed on a Neonatal Intensive Care Unit to measure in-plane rotation which is a common problem with neonatal MRI. Rotational data has been acquired in real-time from phantoms simultaneously with MR images which shows that the wireless accelerometer can be used in close proximity to the MR system. No artifacts were observed on the MR images from the accelerometer or from the MR system on the accelerometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The third paper by Paley et al [3] used a wireless accelerometer in conjunction with a dedicated 3T neonatal MRI system installed on a Neonatal Intensive Care Unit to measure in-plane rotation, which is a common problem with neonatal MRI. Rotational data were acquired in real-time from phantoms simultaneously with MR images, which showed that the wireless accelerometer could be used in close proximity to the MR system.…”
mentioning
confidence: 99%
“…The third paper by Paley et al [3] used a wireless accelerometer in conjunction with a dedicated 3T neonatal MRI system installed on a Neonatal Intensive Care Unit to measure in-plane rotation, which is a common problem with neonatal MRI. Rotational data were acquired in real-time from phantoms simultaneously with MR images, which showed that the wireless accelerometer could be used in close proximity to the MR system.…”
mentioning
confidence: 99%